Optimalisasi Manfaat Jaminan Kehilangan Pekerjaan (JKP) Bagi Karyawan PKWT - Humairoh Tazkiyatun Nisa; Guruh Novan Aldianto; Eka Saputra (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Social security is a welfare guarantee regulated by the government in providing benefits for workers / laborers and their family members. There are several social security programs which include, Work Accident Insurance; Death Guarantee; Pension Security; Old Age Guarantee; Health Insurance and the latest scheme is Job Loss Insurance. As one of the government's efforts in helping the welfare and protection of workers / laborers if affected by Termination of Employment (ToE). This article discusses the polemical background of the development of the job loss insurance program in Indonesia, especially on the provision of job loss insurance benefits for workers who are laid off with expired contract periods. The research method used is the study of literature. As for job loss guarantees, there are still some problems that arise among the community in receiving benefits that are only given to certain criteria, namely being affected by termination of employment (ToE) due to resignation. As a suggestion from this study, this job loss guarantee scheme needs to be reviewed and socialized that can be adjusted to market conditions in receiving benefits from the program.